2015
DOI: 10.1007/s10198-015-0757-y
|View full text |Cite
|
Sign up to set email alerts
|

Economic burden of toxicities associated with treating metastatic melanoma in eight countries

Abstract: BackgroundInformation on costs of managing adverse events (AEs) associated with current treatments in metastatic melanoma is limited. This study estimates costs of AEs in eight countries: Australia (AU), Canada (CA), France (FR), Germany (GE), Italy (IT), the Netherlands (NL), Spain (ES), and the UK.MethodsA literature search was conducted to identify grade 3/4 AEs from product label, published trials, conference abstracts, and treatment guidelines. Resource utilization for the management of each type of AE wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 22 publications
1
39
0
Order By: Relevance
“…The study by Nuijten et al was considered as a duplicate of the study by Banz et al The literature research was then extended to the management of AEs related to treatment in melanoma, considering that the management of grades 3 and 4 AEs does not depend on the underlying disease. Two studies were identified 19 , 20 and none was excluded. French experts were asked to complete data when information was lacking.…”
Section: Methodsmentioning
confidence: 99%
“…The study by Nuijten et al was considered as a duplicate of the study by Banz et al The literature research was then extended to the management of AEs related to treatment in melanoma, considering that the management of grades 3 and 4 AEs does not depend on the underlying disease. Two studies were identified 19 , 20 and none was excluded. French experts were asked to complete data when information was lacking.…”
Section: Methodsmentioning
confidence: 99%
“…The cost parameters were associated with the management and treatment of adverse events in the patients affected by metastatic melanoma, following the administration of one of the above-mentioned innovative treatments. Table 4 reports the cost estimates obtained from two studies through a systematic review of the literature carried out internationally [27,28]. For the adverse event 'pneumonia', the model takes into account the Italian national tariff associated with DRG 90 (simple pneumonia and pleurisy, age > 17 years, without complications) [29].…”
Section: Cost Parametersmentioning
confidence: 99%
“…Comparing PEMBRO with IPI in controlled trials, PEMBRO as a single agent demonstrated prolonged progression-free and overall survival with fewer high-grade adverse events 6 , and NIVO administered in combination with IPI has better progression free survival and higher rates of objective response than with IPI alone 7 . Costs related to toxicity can be substantial, particularly with respect to inpatient management of AEs [11][12][13] . In clinical trials, reported grade 3 or 4 treatment-related adverse events (AEs) are 59% with IPI þ NIVO in combination and 17% with PEMBRO as a single agent 6,7 .…”
Section: Introductionmentioning
confidence: 99%